FRI0440 Trends in rheumatoid arthritis related resource utilization in british columbia, canada: A population based cohort study. (23rd January 2014) - Bansback, N.; Fu, E.; Sun, H.; Guh, D.; Anis, A.; Lacaille, D.
Abstract : Background: RA related health resource use and direct costs may be influenced by prevalence, disease management, and available medications, and understanding trends is crucial for policy makers. Previous costing studies in RA have been limited by unrepresentative RA populations, small numbers, lack of costing data and relatively short follow-up. Objectives: To determine the trend in components of resource utilization in a large, representative, RA cohort based on administrative health data. Methods: RA patients were identified for each fiscal year from 1996/97 to 2004/05 if they had at least two rheumatologist visits with an RA diagnosis, one in the study year and another in a span from the previous to the following year, using administrative health data from British Columbia. The costs of drugs, physician visits and hospitalizations were calculated from administrative data records using standard procedures and inflated to 2005 Canadian dollars. Results: The number of patients identified increased steadily from 6, 525 in 1996/97 to 10, 068 in 2004/05. A total of 22, 756 individuals with RA provided 71, 200 person-years of follow-up. While annual total costs for this RA cohort increased from 13.5M in 1996 to 33.0M in 2004/05, the annual cost per person year increased from 2, 077 to 3, 289 (Figure 1 ). The proportion of costs attributable to hospitalizations markedly decreased (from 59.4% to 21.1% of the total per person annual cost), while since 2001 the proportion of costs attributable to medications has increased, predominantly through biologics which have grown from 17.4% to 48.4% of the total costs. Conclusions: The type of resources consuming health care dollars has changed dramatically. We are currently in the process of extending this analysis to 2010 data. As decisions are made on future management and policy strategies, understanding causal relationships between components, for example whether increased biologic use has led to reduced hospitalisations will be crucial and is the subject of future research. Disclosure of Interest: None Declared